Pengaruh Pemikiran Ibnu Abbas dalam Perkembangan Tafsir Al-Qur’an - Ahmad Deski (Institut Darul Quran Payakumbuh, 2014)
This article presents about Al-Qur’an, the holly Book of Muslims. Al-Qur’an is a guide for human beings to run their lives in the world. Al-Qur’an has values or directions for regulating everything from small problems up to big deals. Mufassirs had paid their much attention and effort to explore glorius values within the Al-Qur’an. Ibnu Abbas was a popular and honorable mufassir during the periode of prophet’s era due to his broad knowledge and accurate analysis in interpreting the verses of Al-Qur’an. He, even, was called by many titles like; bahr al ‘ilm (the ocean of knowledge), habr al ummah (ulama of human beings), turjuman al Qur’an(translator of Al-Qur’an), rais al mufassirun (the leader of mufassirs), and al bahr (Ocean).Next, Ibnu Abbas was also as a pioneer of interpretation theory which bore many interpretation models at the next periodes. His ideas were believed as the most accurate model among mufassir bil ma’tsur as well asmufassir bi al ra’yi. He, traditionally, even was trusted as a succesful great man who grew up an embrio of Hermeneutika al-Qur’an.